Level of Depression, Anxiety, and Stress of College Students in Indonesia during the Pandemic COVID-19 - Nurul Romadhona; Susan Fitriyana; Raden Ganang Ibnusantosa; Titik Respati (Global Medical & Health Communication (GMHC), 2021)
The COVID-19 pandemic has caused a shift in learning methods to online. The obstacles felt by college students can have an impact on mental health. However, data on student mental health in Indonesia during the pandemic is still limited. This study describes the depression, anxiety, and stress of college students in Indonesia during the COVID-19 pandemic. This research method is descriptive, conducted on college students in Indonesia from July to August 2021. Sampling is done by voluntary sampling collection, with 258 respondents. The research instrument is a questionnaire of characteristics and depression, anxiety, stress scale (DASS) 42 in the form of Google Form. Data analysis using Microsoft Excel. The results of the research on the characteristics of the most respondents, namely, age in the range of 20–24 years (85.3%), female (64.7%), from Java (60.8), third grade (66.7%), living with parents (74.8%), and from the faculty of medicine (23.3%). More college students are not depressed (55.0%) or not stressed (57.4%) than those who are depressed or stressed. However, more college students experience anxiety than those who are not anxious, 60.1%. Based on the level, most college students experienced moderate depression (12.8%), very severe anxiety (20.9%), and severe stress (13.6%). This study concludes that most college students experience moderate depression, very severe anxiety, and severe stress. The success of online education depends on several factors, such as basic technical skills and the ability to access hardware and software, good self-motivation, and the availability of a conducive learning environment. This problem can have an impact on the mental health of college students. TINGKAT DEPRESI, KECEMASAN, DAN STRES PADA MAHASISWA DI INDONESIA SELAMA MASA PANDEMI COVID-19Pandemi COVID-19 menyebabkan peralihan metode pembelajaran menjadi daring. Terdapat manfaat dan kendala pada pembelajaran daring. Kendala yang dirasakan mahasiswa dapat berdampak pada kesehatan mental. Data kesehatan mental mahasiswa di Indonesia selama pandemik masih terbatas. Penelitian ini bertujuan menggambarkan depresi, kecemasan, dan stres pada mahasiswa di Indonesia selama masa pandemi COVID-19. Metode penelitian adalah deskriptif yang dilakukan pada mahasiswa di Indonesia pada Juli hingga Agustus 2021. Pengambilan sampel dengan cara sampling sukarela dengan jumlah responden 258 orang. Instrumen penelitian berupa kuesioner karakteristik dan depression, anxiety, stress scale (DASS) 42 dalam bentuk Google Form. Analisis data menggunakan Microsoft Excel. Hasil penelitian karakteristik responden yang terbanyak, yaitu usia pada rentang 20–24 tahun (85,3%), perempuan (64,7%), berasal dari Pulau Jawa (60,8), tingkat tiga (66,7%), tinggal bersama orangtua (74,8%), dan dari fakultas kedokteran (23,3%). Lebih banyak mahasiswa yang tidak depresi (55,0%) atau tidak stres (57,4%) daripada yang depresi atau stres. Namun, lebih banyak mahasiswa yang mengalami kecemasan daripada yang tidak cemas, yaitu 60,1%. Berdasar atas tingkatannya, mahasiswa paling banyak mengalami depresi sedang (12,8%), kecemasan sangat berat (20,9%), dan stres berat (13,6%). Simpulan penelitian ini adalah sebagian besar mahasiswa mengalami depresi sedang, kecemasan sangat berat, dan stres berat. Keberhasilan pendidikan daring bergantung pada beberapa faktor seperti keterampilan teknis dasar dan kemampuan mengakses perangkat keras dan lunak, motivasi diri yang baik, serta ketersediaan lingkungan belajar yang kondusif. Terkendalanya hal ini dapat berdampak pada kesehatan mental mahasiswa.